2020
DOI: 10.1088/1755-1315/433/1/012039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of treatment of seeds of grain crops by ultraviolet radiation before sowing

Abstract: Cereals form the most important group of plants cultivated by man. The aim of the work is to study the effect of ultraviolet led emitter in the processing of seeds of grain crops to improve sowing performance. The objects of the study were the seeds of winter and spring wheat, winter triticale, naked oats. Seeds were treated with ultraviolet LEDs in the range of radiation in the UV zone for 5, 10 and 15 minutes, with average illumination energy of 3.137 W/m2. Growth strength, laboratory germination, shoot heig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…According to Kondrateva et al. (2020), exposure to UV radiation had a positive impact on wheat germination. The authors reported that a 10 min exposure to UV with a dose of 188.2 mJ/cm 2 led to an increase in the growth strength and germination rate of tested winter wheat.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Kondrateva et al. (2020), exposure to UV radiation had a positive impact on wheat germination. The authors reported that a 10 min exposure to UV with a dose of 188.2 mJ/cm 2 led to an increase in the growth strength and germination rate of tested winter wheat.…”
Section: Resultsmentioning
confidence: 99%
“…The authors reported that a 10 min exposure to UV with a dose of 188.2 mJ/cm 2 led to an increase in the growth strength and germination rate of tested winter wheat. However, their study employed primarily UV‐A radiation that has less lethality compared to UV‐C (Kondrateva et al., 2020). In another investigation, it was observed that exposing corn kernels to UV‐C radiation (254 nm) with a dose of 5000 mJ/cm 2 did not have a negative effect on the kernels’ ability to germinate (Popović et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The technique of direct electrochemical oxidation of blood has been developed, which does not require the use of antibiotics in the treatment of animals. For the first time [8,9,10] the process of electrochemical oxidation of blood inside a blood vessel was performed. The chlorine ion, which is part of the sodium chloride in the blood plasma, is oxidized.…”
Section: аннотацияmentioning
confidence: 99%
“…There are many ways to remove seeds from a dormant state. In the literature [5], seed germination is activated with the help of environmentally safe and inexpensive ultraviolet radiation. Song L., Wang Q., and other scientists [6] investigated the effect of g-irradiation on the germination energy of rice seeds, estimated using infrared spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Kondrateva N. P., Kasatkina N. I., Kuryleva A [9] showed a positive effect of ultraviolet irradiation on the awakening of grain seeds. Kondrateva N., Rudenok V., Kasatkina N. [13] obtained a synergistic effect from simultaneous exposure to ultraviolet radiation and a nanosilicon preparation to increase the germination rate of seeds. Therefore, the search for new methods of pre-planting seed treatment, ensuring an increase in their yield, is an urgent task.…”
Section: Introductionmentioning
confidence: 99%